2015
DOI: 10.1094/pdis-08-14-0865-re
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Yr26-Virulent Races of Puccinia striiformis f. tritici Are Threatening Wheat Production in the Sichuan Basin, China

Abstract: 21

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 33 publications
0
48
0
Order By: Relevance
“…Arrows indicate wheat-rye 1BL•1RS translocation chromosomes . Han et al (2015) concluded that more than 76 % of wheat cultivars and breeding lines from the Sichuan Basin are susceptible to the V26/Gui 22 race at the seeding stage. It is, therefore, urgent to identify new stripe rust resistance genes and to use more effective genes to counterbalance the continuous evolution of rust pathogens in wheat-breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…Arrows indicate wheat-rye 1BL•1RS translocation chromosomes . Han et al (2015) concluded that more than 76 % of wheat cultivars and breeding lines from the Sichuan Basin are susceptible to the V26/Gui 22 race at the seeding stage. It is, therefore, urgent to identify new stripe rust resistance genes and to use more effective genes to counterbalance the continuous evolution of rust pathogens in wheat-breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…Wheat stripe rust is one of the most serious wheat diseases. Therefore, stripe rust resistance gene Yr26 has been widely used in wheat breeding programs since its discovery in the early 1990s [1]. However, dependence on a single gene can be risky, as the rise of new virulent strains (such as the Yr26 -virulent race V26/Gui 22) can easily lead to a significant decline in wheat production.…”
Section: Introductionmentioning
confidence: 99%
“…However, dependence on a single gene can be risky, as the rise of new virulent strains (such as the Yr26 -virulent race V26/Gui 22) can easily lead to a significant decline in wheat production. Yr26 virulence may represent a major threat to wheat production in the Sichuan Basin and other regions of China [1]. The use of cultivars harboring novel resistance is an efficient and economical alternative to control wheat stripe rust [2].…”
Section: Introductionmentioning
confidence: 99%
“…Cultivation of resistant varieties is the most effective, economical, and environmentally friendly way to control the disease. Although many resistance genes have been identified and utilized in wheat cultivars (Cheng et al, 2014; Lu et al, 2014; Han et al, 2015), the protection conferred has not been durable due to genetic variation in the pathogen population. One example is that of resistance gene Yr26 that was widely used in Chinese wheat breeding in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…One example is that of resistance gene Yr26 that was widely used in Chinese wheat breeding in recent years. New Yr26 -virulent (CYR34, V26) races are now increasing and are causing unacceptable levels of disease on many of the cultivars with Yr26 (Han et al, 2015). Although resistances governed by quantitative trait loci (QTL) confer a broader-spectrum resistance, the level of resistance is not adequate to prevent significant crop losses, especially under severe epidemic conditions (Niks et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%